Observations sur la situation politique de la Polynesie Francaise au travers de quelques principies de bonne Gouvernance enonces par le PNUD 1997 et le Pacific Plan 2006-15 - Sage, Yves-Louis (Victoria University of Wellington Law Review, 2008)
Since 2004, the political situation in French Polynesia has been marked by chronic instability. Waves of electoral reform initiatives undertaken by the government in order to improve political life have not been successful. This is not surprising since these reforms have been adopted without appropriate consultations with the population and often against the wishes of the local assembly. As a result, these reforms have in fact accentuated the problems they were supposed to resolve. This situation, criticised by a large majority of Polynesian voters, is the result of the violation by the principal political actors in French Polynesia of the principles of good governance developed by the United Nations Development Programme in 1997 and by the Pacific Islands Forum in the Pacific Plan 2006-15. Yet, these are not unsolvable problems should the political actors show the will to tackle them efficiently.